“Apa yang Siswa Pikirkan Tentang Matematika?” Analisis Sentimen pada Siswa Kelas Tinggi Sekolah Dasar - Widyastuti, Widyastuti; Dasari, Dadan; Noer, Sri Hastuti (Jurnal Pendidikan Matematika Universitas Lampung, 2024)
The purpose of this study was to describe a sentiment model for elementary school students' comments on mathematics. Respondents in this study were 286 elementary school students in seven elementary schools in Bandar Lampung. Sentiment data were obtained through student comments that were collected in May-June 2024. Data analysis used sentiment analysis and mood analysis based on student comment texts carried out using Ekman's Basic Emotions classification. The analysis was carried out through Orange software using Corpus analysis, sentiment analysis, topic modeling, and also tweet profiler. The results of the analysis revealed that: i) the sentiment of elementary school students was dominated by positive sentiment (percentage achievement of 50%), with the three most keywords expressed in students' textual comments about mathematics were "fun", "difficult", "hard"; ii) the sentiment displayed by grade 5 and grade 6 students was dominated by positive sentiment while grade 4 students predominantly caused negative sentiment; and iii) the results of Ekman's Basic Emotions classification showed that "Joy" was the most dominant emotion felt by students in their textual comments about mathematics, while "fear" was the emotion with the least occurrence in students' textual comments about mathematics. The implications of the finding for the model of positive sentiment of elementary school students towards mathematics which can be used as a basis for selecting research interventions and mathematics learning strategies/methods that are more appropriate for elementary school students.